Insurance and Its Business in Nepal - Gurung, Jas Bahadur (Journal of Nepalese Business Studies, 2012)
This study aims mainly to analyze the performance of insurance business in Nepal. The data used in this study is mainly quantitative and analysis has been carried out by using simple percentage and correlation coefficient. The study reveals that there are altogether 25 insurance companies viz. 8 life insurance and 16 non-life insurance and one offer both life and non-life services. They have altogether 340 branch offices in Nepal. The growth of insurance policies for both life and non-life insurance companies has been increasing and significant during the study period. Similarly, the progressive trend of premium collection reached to 48 percent for non-life and 37.06 percent for life insurance in FY 2066/67 and contributed 1.70 percent in GDP of the economy. Moreover, the investment of insurance companies has been positive but fluctuating over the period under study. However, the correlation coefficient between total premium collection and total investment is positive with r=0.97 and significant as its PE is only 0.0163. These facts reveal that the performance of insurance business in Nepal is satisfactory. The Journal of Nepalese Business Studies Vol. Vii, No. 1, 2010-2011 Page : 70-79 Uploaded date: July 8, 2012